Socialization Tactics, Employee Proactivity, and Person-Organization Fit. - Kim, Tae‐Yeol; Cable, Daniel M.; Kim, Sang-Pyo (Journal of Applied Psychology, 2005)
This study examined the linkage between organizational socialization tactics and person-organization (P-O) fit and examined the moderating influence of employees' proactivity behaviors. Results from a sample of 279 employee-supervisor pairs from 7 organizations in South Korea revealed a positive relationship between institutionalized socialization tactics and P-O fit perceptions. However, the association between firms' socialization tactics and P-O fit was facilitated or negated by several proactive behaviors that employees used to gain control over their environment. For example, employees' positive framing harmonized with institutional tactics to create higher P-O fit, whereas employees who proactively developed strong relationships with their supervisors essentially replaced institutionalized socialization tactics.